2012
DOI: 10.1111/j.1471-3802.2012.01234.x
|View full text |Cite
|
Sign up to set email alerts
|

‘My colleagues wear blinkers . . . If they were trained, they would understand better’. Reflections on teacher education on inclusion in Cyprus

Abstract: This paper discusses fundamental theoretical issues in relation to education on inclusion. These issues inform core decisions about initial teacher education courses and in-service teacher-training programmes on inclusion. International and local discussions and research in this area formed the background for the design and implementation of a 2-year funded research project whose aim was to record teachers' knowledge, attitudes and skills in relation to inclusion before developing an in-service training progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 29 publications
0
12
0
3
Order By: Relevance
“…Awareness of teachers' preferences and needs with regard to course design may allow for more refined choices and decisions about course content and format, which, in turn, may increase their perceived preparedness for inclusion of dyslexic learners. Studies relating to both the initial teacher training (e.g., Sharma & Sokal, ) and continuing professional development context (e.g., Symeonidou & Phtiaka, , ) stress that in order to boost positive attitudes, self‐efficacy beliefs and self‐confidence, teacher training courses should address possible concerns that trainees may have about the practical aspects of implementing inclusive practices.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Awareness of teachers' preferences and needs with regard to course design may allow for more refined choices and decisions about course content and format, which, in turn, may increase their perceived preparedness for inclusion of dyslexic learners. Studies relating to both the initial teacher training (e.g., Sharma & Sokal, ) and continuing professional development context (e.g., Symeonidou & Phtiaka, , ) stress that in order to boost positive attitudes, self‐efficacy beliefs and self‐confidence, teacher training courses should address possible concerns that trainees may have about the practical aspects of implementing inclusive practices.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, the importance and effectiveness of adequate professional teacher training in increasing this background knowledge has been stressed in previous studies (e.g., Brady et al, ; Goldfus, ; Kahn‐Horwitz, , ; McCutchen et al, ; Podhajski et al, ). Considerable attention was given to researching general pre‐service and in‐service teacher education towards inclusion (e.g., European Agency for Development in Special Needs Education, ; Robinson, ) and verifying the effectiveness of various types of teacher training with a view to increasing teacher self‐efficacy in implementing inclusive instructional practices, enhancing positive attitudes, and reducing concerns towards inclusion (e.g., Campbell, Gilmore, & Cuskelly, ; Chao, Forlin, & Ho, ; Florian, ; Forlin et al, ; Lai, Li, Ji, Wong, & Lo, ; Peebles & Mondaglio, ; Sharma & Sokal, ; Symeonidou & Phtiaka, , ). However, few studies are available that focus on the EFL teacher knowledge of inclusive education principles, inclusive instructional practices, the nature of SEN, and SpLDs (dyslexia in particular) as well as on EFL teachers' professional training needs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Cyprus, children with disabilities were traditionally placed in segregated settings, a process that began in 1929 with the establishment of the School for the Blind and numerous other special schools and institutions (Phtiaka, 2007). This form of segregation remained in place until the unofficial practice of integration in the early 1980s, when children were placed in mainstream educational environments through the organisation of special education settings within them (Symeonidou & Phtiaka, 2012). Integration was passed into law in 1999, with the Education Act for Children with Special Needs (113(I)/99), which has a rhetoric of accessibility, equal rights and opportunities for all.…”
Section: The Study's Contextmentioning
confidence: 99%
“…Critiques of the law indicated that its content proposes discriminatory practices, which allow for the perpetuation of the dyadic educational system, special and the mainstream, thereby permitting the latter to remain unaltered in terms of culture and pedagogy (Pieridou, 2013). This, often, leaves special teachers responsible for children identified as having special educational needs, while the mainstream teachers' role in both pre-primary and primary settings remains unchanged; mainly due to the absence of in-service teacher education training programmes on inclusion and appropriate teaching techniques for a diverse learner population (Pieridou, 2013;Symeonidou & Phtiaka, 2012).…”
Section: The Study's Contextmentioning
confidence: 99%
“…In Cyprus inclusive education is a human right, as not yet guaranteed, for SEN pupils (Symeonidou, 2018). A law implemented in 1999 was drafted to deal with this issue (N.113(I)/99), but despite some progress being made in the secondary education system that has encouraged inclusion, the practical implementation of the existing regulations still results in SEN pupils, experiencing marginalization (Symeonidou & Phtiaka, 2014).…”
Section: Introductionmentioning
confidence: 99%